Study on imbibition during the CO2 enhanced oil recovery in fractured tight sandstone reservoirs - Yuxia Wang; Qinghua Shang; Jingzhe Guo; Lifa Zhou (Capillarity, 2023)
CO2 enhanced oil recovery (CO2-EOR) is a key technology for improving the oil recovery of fractured tight reservoirs, and imbibition has been recognized as an important mechanism for oil recovery in low-permeability reservoirs. To clarify the imbibition role and influencing factors during the CO2-EOR process in fractured tight oil reservoirs and also improve the EOR mechanism, a high-temperature and high-pressure CO2 imbibition experiment was performed based on the nuclear magnetic resonance technology. The results show that high pressure and high permeability are beneficial to imbibition efficiency. The salinity of the imbibition fluid is not very sensitive to the imbibition recovery. In addition, the CO2 increases the imbibition speed and can also significantly improve the production rate and oil recovery. It is beneficial to increase the CO2 concentration to shorten the imbibition equilibrium time and enhance oil recovery. According to the results of the nuclear magnetic resonance study, although the nanopore can provide a greater imbibition force, the oil flow resistance is also larger, but CO2 can reduce the flow resistance of oil and be conducive to oil production in smaller pores. The inclusion of imbibition into the research category of CO2-EOR mechanism will be more in line with field practice and more scientific in fractured tight reservoirs, thus providing theoretical support for the development and improvement of the CO2-EOR technology. Document Type: Original article Cited as: Wang, Y., Shang, Q., Guo, J., Zhou, L. Study on imbibition during the CO2 enhanced oil recovery in fractured tight sandstone reservoirs. Capillarity, 2023, 7(3): 47-56. https://doi.org/10.46690/capi.2023.06.02